From the Journal Editor - Peace, Christopher (New Zealand Journal of Health and Safety Practice, 2024)
Research papers In this edition we are delighted to publish an applied research article report on “exposure to dust and bioaerosols at GB municipal waste handling sites” by Keen, Sandys & Crook, three leading scientists from the British Health and Safety Laboratory. Internationally, the waste industry is very hazardous; this article makes a major contribution to our occupational health knowledge in New Zealand. It should be circulated to officers and senior managers in the New Zealand waste industry. It may also suggest areas for applied research and investigations. Other research articles in this issue also touch on occupational health. An article by Koia gives an interesting perspective on strategic management of work health and safety, including issues for the New Zealand government as it reviews submissions on proposed reforms. HASANZ Conference 2024 In September 2024, the Health and Safety Association of NZ held its biennial conference in Wellington. The official conference opening in the Beehive was addressed by the Hon Brooke van Velden, Minister for Workplace Relations and Safety and brought together many attendees in a social setting. The Minister referred to the-then current consultation on proposed reform of the health and safety system (Van Velden, 2024) that led to 10 articles in the second edition of this journal available at https://ojs.victoria.ac.nz/nzjhsp/issue/view/1006). Over the two-days of the conference attendees could listen to four keynote speeches, choose from 18 presentations in six concurrent sessions, listen to a panel discussion, and attend discipline specific sessions. Attendees could also inspect a wide range of posters and engage with diverse stands. Complementing the article by Keen, Sandys & Crook were poster displays on use of the dust lamp by Levinge and combustible dust explosions by Yu. This edition of New Zealand Journal of Health and Safety Practice contains some of the abstracts and posters. We hope they will lead to full reports in due course but here they help make the conference “the conference that keeps on giving”. Case study To complement the article by Keen, Sandys & Crook, the New Zealand Institute of Safety Management (NZISM) has kindly given permission for a case study paper on the waste industry, originally published in 2021, to be reprinted in this edition. Some of the sources cited were written by or contributed to by Keen, Sandys & Crook. The paper was research for a webinar for NZISM and carries a warning that it has not been reviewed and may be out of date in places, especially in relation to cases in the District Court on work health and safety. For 2025 In April 2025 we plan to publish a special edition to mark International Workers Memorial Day. Submissions on work-related death are welcome and should be submitted by 10 March 2025. The New Zealand Occupational Hygiene Society (NZOHS) is calling for conference abstracts and papers about work-related health for its conference on 26-28 May 2025. The focus should be on occupational exposures, associated health effects and occupational health research. We hope to publish the papers and abstracts later in 2025. Contact events@nzohs.org.nz for further information.